(3CSGSjGJ GdJfXje hGdEOGQI (B/s - (3CHh bMa, YHO GdSdGes ((3HjQhJ(B: s (3OGQGdeYQaI GdLGeYjI(B, s, 2001)
(3ebOeGJ CSGSjI(B- (3eaghe GdEOGQI hCgejJgG GdfSHjI(B- (3JWhQ GdacQ GdEOGQj(B- (3GdeOjQhf(B-(3EJNGP GdbQGQGJ hMd GdeTcdGJ(B- (3hXGFa efXeGJ GdCYeGd hGdHjFIs
Keywords: (3GJNGP GdbQGQGJs; (3GdEOGQIs; (3JfXje hGOGQIs